Tony Redmond’s Microsoft Exchange server 2003 with SPI - Redmond, Tony (Elsevier/Digital Press, 2005)
The new edition features key updates based on practical experience of working with Exchange 2003 since its release, including Service Pack 1 (SP1), plus detailed description of the new functionality included in Exchange 2003 and Outlook 2003